2018
DOI: 10.1038/s41598-018-34821-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the secondary plant metabolite Cucurbitacin B on the demographical traits of the melon aphid, Aphis gossypii

Abstract: Cucurbitacin B is a natural triterpene present in plants of Cucurbitaceae family, which are among the host plants for melon aphid, Aphis gossypii. In present study we characterized the effects of two cucurbitacin B concentrations on the biological parameters of adults (F0) and of juveniles and adults of their progeny (F1). The results showed that cucurbitacin B at 25 ppm significantly reduced the adult longevity and fecundity of both F0 and F1 generation. Exposure of F0 generation to 25 ppm though reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…The pre-adult period and mean generation time ( T ) were increased due to different physical and chemical processes when treated with buprofezin. Similar effects at the demographical level have been presented in various other reports 29,30,65,66 . Previous reports suggested that exposure to sublethal concentrations of buprofezin can suppress the population growth of S .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pre-adult period and mean generation time ( T ) were increased due to different physical and chemical processes when treated with buprofezin. Similar effects at the demographical level have been presented in various other reports 29,30,65,66 . Previous reports suggested that exposure to sublethal concentrations of buprofezin can suppress the population growth of S .…”
Section: Discussionsupporting
confidence: 88%
“…furcifera via impact on their survival and reproduction 29,30 . Additionally, adverse effects at the demographical level have been reported in melon aphid at 25 and 100 ppm of cucurbitacin B 65 . Moreover, sublethal concentrations of imidacloprid and pirimicarb decreased the longevity and population growth of A gossypii 67 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to various physical and chemical processes, the pre-adult and mean generation time (T) increased after exposure to MB. In a few other studies on A. gossypii, similar effects were reported at the demographic level [12,55].…”
Section: Discussionsupporting
confidence: 71%
“…For comparison, we ran the same bioassays using adults of the common pest cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae), as prey. This insect is highly polyphagous, found in greenhouse and field vegetables, fruit crops, and ornamentals (Blackmen & Eastop, 2000; Capinera, 2001; Yousaf et al, 2018). Its direct feeding causes leaf chlorosis and deformity, as well as sticky honeydew which provides a growth medium for sooty mold which reduces the plant’s photosynthetic capacity; the aphid also transmits various plant‐pathogenic viruses (Yuan & Ullman, 1996; Alford, 1999; Capinera, 2001; Pinto et al, 2008; Campolo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%